If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11(x+6)=13x+10
We move all terms to the left:
11(x+6)-(13x+10)=0
We multiply parentheses
11x-(13x+10)+66=0
We get rid of parentheses
11x-13x-10+66=0
We add all the numbers together, and all the variables
-2x+56=0
We move all terms containing x to the left, all other terms to the right
-2x=-56
x=-56/-2
x=+28
| x-3.25=8 | | v−18.93-1=-0.75 | | 2(w+15)=78 | | -4=-2+2w | | 4=4z−8 | | x=(x+65) | | -20z-10=-20z+16+1 | | j3+ 6=10 | | 9(-6k-19)-4=-19k | | 7x+4=2(3x+5) | | -25=u/4+3 | | a+3=(a-1) | | -(w+2)=5w | | -22=4x+6=50 | | 1/4(32/9)=z | | -6+4x=-30 | | |x-5|+3=9 | | 80=8-9v | | 185=62-y | | 12(x+5)=96 | | |x+5|+3=9 | | 10+-2/3x=52 | | 5p+9−5p=8 | | -5y-14=16 | | .5x+4=-3.5+3.5x | | 9x+16=-20 | | -8+2x=-13-3x | | 3^4-x=8 | | -5x+9=4x-18 | | -2(8r-4)=8-16r | | 7^3x-5=84 | | 6=1/2(27)+b |